The Impact of Active Methodologies and External Examination on Students’ Motivation - Coutinho, Isabel Ribau (Advances in Social Sciences Research Journal, 2023)
Assessment plays a significant role in the learning and teaching process. In Portugal, external examinations are vital to students’ transition to the higher education system. To access engineering, science, and health courses is mandatory to do the national examination for “Physics Chemistry A” which occurs after 11.º grade. Grounded on the social cognitive perspective, the research’s main goal was to analyze the impact of the laboratory station methodology and flipped classrooms on the motivation and resilience to continue in the science field and to perceive the impact of external examination on motivation. The data analysis allows us to conclude that this teaching and learning methodology plays a significant role in the maintenance of motivation. Secondly, data showed a positive effect of the intervention on student performance. Thirdly the external examination frames students’ motivation guide type. Fourth, these active methodologies consolidate the student’s learning strategies and are reflected in the external examination.